2021
DOI: 10.1002/bse.2768
|View full text |Cite
|
Sign up to set email alerts
|

What drives the adoption and consumption of green hotel products and services? A systematic literature review of past achievement and future promises

Abstract: The current study utilises the time-tested systematic literature review (SLR) method to identify and analyse 76 studies addressing the consumer adoption of green hotels.The results of the research profile analysis show that the literature on consumers' adoption and consumption of green hotel products and services is expanding and gaining more recognition from researchers working in Asian contexts, particularly China, Taiwan and India. Moreover, the qualitative thematic analysis yields four key themes, (a) cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 98 publications
2
26
1
Order By: Relevance
“…A consolidated review of past literature assists in better conceptualization, and the identified future research directions help advance the domain. It also provides a quick reference for domain practitioners to craft their offerings accordingly, design their processes and adopt strategies (Arun et al, 2021; Kushwah et al, 2019). With rising interest in shared consumption, scholars have identified many factors determining the adoption of shared consumption.…”
Section: Introductionmentioning
confidence: 99%
“…A consolidated review of past literature assists in better conceptualization, and the identified future research directions help advance the domain. It also provides a quick reference for domain practitioners to craft their offerings accordingly, design their processes and adopt strategies (Arun et al, 2021; Kushwah et al, 2019). With rising interest in shared consumption, scholars have identified many factors determining the adoption of shared consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the environmental approaches in nonservice industries (e.g., public sectors), consumers with more awareness of their impact on the environment expect the hotels they interact with to do their part for the environment (Chung, 2020). Accordingly, considering that hotels face increasing pressure to pay more attention to environmental issues, "green hotels and green initiatives in hotels are quickly becoming the norm" (Arun et al, 2021(Arun et al, , p. 2638. For example, most hotels have provided environmentally oriented guidelines to employees, which aim to develop and implement environmental initiatives throughout hotel companies (Chan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Green consumption is often driven by social motivations, such as impression management, whereby consumers seek to present a positive self-image to others by supporting environmental protection causes and purchasing green products that are believed to have a positive impact on environment (Arun et al, 2021). However, green consumption involves self-sacrifice as green products are typically more expensive and of lower quality than regular products, leading consumers to forgo personal gains (Gupta & Ogden, 2009).…”
Section: The Role Of Impression Management Motivationmentioning
confidence: 99%